Local–global linkages: Challenges in organizing functional communities for ecosocial justice. Issue 3 (2nd October 2019) - Izlar, Joel
ABSTRACT: Communities face "glocalized" ecosocial problems. Functional Community Organization bridges local problems with globalized issues, organizes community, and meets need. Models describe glocal linkages and their outcomes, but little is known of processes and challenges in organizing. This article qualitatively explores ecosocial organizing challenges in a Community Technology Center in a US city, which organized around e-waste and digital inequality. Findings indicate that Functional Communities may face challenges in organizing aims due to complexities in balancing need while concurrently addressing global problems and issues in structure, funding, and process. This may be mitigated through communication, focus, self-awareness, and reflexivity.